Accelerated Hypofractionated Radiotherapy for Centrally Located Lung Tumours Not Suitable for Stereotactic Body Radiotherapy or Chemoradiotherapy. Issue 2 (February 2023) - Zeng, K.L.; Poon, I.; Ung, Y.; Tsao, M.; Zhang, L.; Cumal, A.; Louie, A.V.; Cheung, P.
Abstract: Aims: Accelerated hypofractionated radiotherapy is used at our institution for non-small cell lung cancer (NSCLC) patients not eligible for stereotactic body radiotherapy or chemoradiotherapy. The purpose of this study was to report clinical outcomes of delivering 60 Gy in 15 fractions for these patients. Materials and Methods: All NSCLC patients who received 60 Gy in 15 fractions were reviewed. Outcomes of interest were local failure, regional failure, distant progression, overall survival and treatment-associated toxicities. Results: In total, 111 patients were included. The median age was 78.8 years and most tumours were adenocarcinoma ( n = 55, 49.6%). Sixty-five patients (58.6%) were N0. The cumulative incidence of local failure at 12 and 24 months in the N0 cohort was 5.2% and 14.2%, respectively, compared with 11.5% and 14.8% for N+ patients. Tumour size >35 mm predicted for local failure (hazard ratio 2.706, 95% confidence interval 1.002–7.307, P = 0.0494). Distant progression at 12 and 24 months in N0 patients was 13.7% and 24.3% compared with 24.6% and 33.5% in N+ patients. In N0 patients, larger tumour size was associated with increased risk of distant progression. The median overall survival was 38.1 months in N0 patients versus 31.7 months in N+ patients. The most common toxicity was radiation pneumonitis ( n = 6, 6.4%). The incidence of any grade 3 toxicity was 10.3% at ≥1 year. There were no deaths or hospitalisations attributed to treatment. Conclusions: Accelerated hypofractionated radiotherapy is well tolerated and resulted in favourable clinical outcomes in various stages of NSCLC patients. Highlights: Patients with NSCLC ineligible for SBRT or chemoradiotherapy can be considered for accelerated hypofractionated radiotherapy. Local control and survival in non-metastatic patients were favourable with this strategy. Grade ≥3 toxicity was uncommon.